Alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol and preparation method and application thereof
A loose polyester nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol, prepared by interfacial polymerization technology, solves the problem of easy hydrolysis of polyester nanofiltration membranes under alkaline conditions, and achieves efficient dye/salt separation in a strongly alkaline environment, which is suitable for dyeing and printing wastewater treatment and salt recycling.
Patent Information
- Application Number
- CN202510913804.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-07-03
AI Technical Summary
Traditional polyester nanofiltration membranes are prone to hydrolysis under alkaline conditions, which leads to a decline in separation performance and makes it difficult to effectively separate dyes and salts, thus limiting their application in strong alkaline cleaning or high-alkalinity wastewater treatment.
2,2,4,4-Tetramethyl-1,3-cyclobutanediol was used as an aqueous monomer and subjected to interfacial polymerization with trimesoyl chloride in the presence of an organic base to form a dense and highly cross-linked polyester separation layer, which enhances the alkali resistance and separation performance of the membrane.
It maintains stable high permeability and efficient dye/salt separation performance under strongly alkaline conditions, making it suitable for dyeing and printing wastewater treatment and salt recycling.
Smart Images

Figure CN120550639B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of membrane separation, and particularly relates to an alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol as well as a preparation method and application thereof. BACKGROUND
[0002] With the rapid development of the textile and printing industries, a large amount of dyes enters water during production and use. The dye wastewater not only has high colority, affecting the light transmittance of water bodies, but also has a complex molecular structure and is difficult to be naturally degraded, thereby posing a long-term threat to the environment and human health.
[0003] As an important separation material, nanofiltration membranes have a wide application in the treatment of dye wastewater and salt mixtures. Nanofiltration is a membrane filtration technology between reverse osmosis and ultrafiltration, which can accurately separate small molecules through size sieving and electrostatic effects at a low operating pressure. Through nanofiltration separation of dyes and salts, not only can environmental pollution be reduced, but also energy and cost can be saved, thereby having a good application prospect in water treatment and the textile industry.
[0004] Traditional polyamide nanofiltration membranes have a dense separation layer, which has a high rejection rate for dyes and salts, so that the salt cannot effectively permeate, and the dyes and salts cannot be effectively separated, thereby being limited in actual application. The polyester loose nanofiltration membrane has a large pore size, a high rejection rate for dyes and a good permeability for salt, and is suitable for the separation of a dye / salt mixed system. The dye molecule usually has a sulfonic acid group and a large size, and is easily rejected by the polyester membrane; and the salt (such as NaCl) exists in the form of ions and has a small size, and can permeate the membrane pores. However, the ester bond (-COO-) in the molecular chain of the polyester membrane is easily hydrolyzed under alkaline conditions, resulting in the destruction of the membrane structure, the increase of the pore size and even the dissolution, thereby reducing the separation performance. This defect of poor alkali resistance limits the application of the polyester nanofiltration membrane in the cleaning of strong alkali or the treatment of high-alkalinity wastewater. Therefore, it is an urgent technical problem to be solved in the field of dye / salt separation to develop a polyester loose nanofiltration membrane with alkali resistance and high permeation selectivity. SUMMARY
[0005] To solve the above technical problems, the application provides an alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol as well as a preparation method and application thereof.
[0006] To achieve the above object, the application provides the following technical scheme.
[0007] One of the technical schemes of the application is as follows:
[0008] The application provides a preparation method of an alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol, which comprises the following steps:
[0009] 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) is dissolved in deionized water containing an organic base, stirred uniformly to obtain an aqueous solution;
[0010] trimesoyl chloride (TMC) is dissolved in n-hexane to obtain an organic phase solution;
[0011] The aqueous solution is poured on the ultrafiltration membrane, soaked, then the remaining aqueous solution is poured out, and the residual liquid on the surface of the ultrafiltration membrane is removed to obtain an ultrafiltration membrane with uniformly distributed aqueous phase on the surface;
[0012] The organic phase solution is poured on the surface of the ultrafiltration membrane with uniformly distributed aqueous phase to perform interfacial polymerization, and after completion, the excess organic phase solution is poured out;
[0013] The ultrafiltration membrane after interfacial polymerization is subjected to heat treatment to obtain the alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol.
[0014] The present application provides a method for preparing a high-selective permeability alkali-resistant polyester loose nanofiltration membrane by interfacial polymerization of 2,2,4,4-tetramethyl-1,3-cyclobutanediol as an aqueous phase monomer and trimesoyl chloride. The aqueous phase monomer TMCD used in the present application has a unique twisted structure and large steric hindrance. At the same time, the addition of an organic base to neutralize the HCl generated in the reaction promotes the transfer of protons in the reaction, forming a dense and uniform polyester separation layer, which has high permeation flux while achieving efficient separation of dyes / salts, and still maintains stable separation performance after soaking in strong alkali for 48 h.
[0015] Further, the mass concentration of the aqueous solution is 0.5-2%;
[0016] And / or, the mass ratio of TMCD to organic base is (1-3):(1-2), for example, the mass ratio of TMCD to organic base is 1:1, 3:1 or 1:2.
[0017] Further, the organic base is selected from one of triethylamine (TEA), tripropylamine (TPA) and N,N-diisopropyl ethylamine (DIPEA).
[0018] Further, the mass percentage of trimesoyl chloride in the organic phase solution is 0.1-0.3%.
[0019] Further, after the aqueous solution is poured on the pretreated ultrafiltration membrane, the soaking time is 1-5 min.
[0020] Further, the interfacial polymerization time is 1-10 min.
[0021] Further, the temperature of the heat treatment is 50-100 DEG C, and the time of the heat treatment is 5-15 min.
[0022] The second technical solution of the present application is:
[0023] The present application also provides a 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based alkali-resistant polyester loose nanofiltration membrane prepared by the above preparation method.
[0024] The third technical solution of the present application is:
[0025] The present application also provides an application of the above 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based alkali-resistant polyester loose nanofiltration membrane in treating printing and dyeing wastewater.
[0026] Compared with the prior art, the present application has the following advantages and technical effects:
[0027] (1) The present application adopts the interfacial polymerization technology, and a dense and high-crosslinking polyester separation layer is formed by the reaction of the water-phase monomer and the organic-phase monomer at the interface, and the operation is simple.
[0028] (2) The present application selects TMCD as the water-phase monomer, and the rigid ring structure of cyclobutane and the tetramethyl substituent provide steric hindrance, improve the rigidity of the polymer chain, and form a dense separation layer. The steric effect of the methyl side group promotes the polymerization to form regular pores, and realizes high-precision separation selectivity.
[0029] (3) The nanofiltration membrane obtained by the reaction of TMCD and trimesoyl chloride under the catalysis of an organic base (such as triethylamine) has low crosslinking degree and large pore size in the separation layer, and can realize efficient separation of dyes and inorganic salts while maintaining high permeation flux.
[0030] (4) The introduction of the special monomer endows the membrane material with excellent alkali resistance and dye / salt separation selectivity. The selectivity layer can improve the ability to resist the erosion of strong alkali solution, and reduce the tendency of hydrolysis of the polyester nanofiltration membrane under strong alkali cleaning. BRIEF DESCRIPTION OF DRAWINGS
[0031] The accompanying drawings, which form a part of the present application, are used to provide further understanding of the present application, and the schematic embodiments of the present application and the description thereof are used to explain the present application, and do not constitute improper limitations on the present application. In the drawings:
[0032] Figure 1 It is a surface scanning electron microscope graph of the original PES ultrafiltration membrane in the present application embodiment 1.
[0033] Figure 2 It is a surface scanning electron microscope graph of the alkali-resistant polyester loose nanofiltration membrane (PE LNF) in the present application embodiment 1.
[0034] Figure 3 ATR-FTIR spectra of the original PES ultrafiltration membrane and the alkali-resistant polyester loose nanofiltration membrane of Example 1 of the present application.
[0035] Figure 4 Plots of permeate flux, Congo red rejection and salt rejection of the polyester loose nanofiltration membrane of Example 1 of the present application for treating four salt and Congo red mixed solutions.
[0036] Figure 5 Plot of normalized pure water flux of the polyester loose nanofiltration membrane of Example 1 of the present application after soaking at different pH for two days.
[0037] Figure 6 Plot of normalized pure water flux of the 1,4-butanediol polyester-based nanofiltration membrane of Comparative Example 1 of the present application after soaking at different pH for two days.
[0038] Figure 7 Plot of feed and filtrate comparison of the PE LNF and 1,4-butanediol polyester-based nanofiltration membrane (BDO-PE LNF) of Example 1 and Comparative Example 1 of the present application after soaking at pH = 14 for two days for filtering Congo solution. DETAILED DESCRIPTION
[0039] Various illustrative embodiments of the present application are described in detail herein below with reference to the attached drawings. These embodiments are listed by way of illustration only and should not be construed to limit the present application, as such, the present application should be construed to encompass any alterations, modifications, rearrangements, substitutions, many embodiments other than those described herein, and any other suitable methods of practicing the present application. The present application is not limited to the embodiments described herein, but includes any other embodiments falling within the scope of the present application.
[0040] It should be understood that the terms used in the present application merely describe particular embodiments and are not intended to limit the present application. In addition, for numerical ranges in the present application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is specifically disclosed. Each smaller range within any stated range or within any stated intermediate value and any other stated value or intermediate value within the stated range is also encompassed within the present application. The upper limit and the lower limit of these smaller ranges can be included or excluded independently from the range.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, preferred methods and materials are described. All publications mentioned in this specification are herein incorporated by reference to disclose and describe the methods and / or materials in connection with which the publications are cited. The citation of any reference in this specification is not intended as an admission that the reference is prior art, but rather that the reference is part of the state of the art.
[0042] Many modifications and variations to the illustrative embodiments described herein will be apparent to those of ordinary skill in the art from the foregoing description. Such modifications and variations are intended to fall within the scope of the present application. Other embodiments will be apparent to those of ordinary skill in the art from consideration of the description and practice of the present application. The description and examples are illustrative only.
[0043] As used herein, the terms "comprises", "comprising", "includes", "including", "has", "having", "contains", "containing", or variations thereof, are intended to be open-ended terms that mean inclusion, but not limited to, the listed material or step.
[0044] The present application uses 2,2,4,4-tetramethyl-1,3-cyclobutanediol as a water phase monomer, and performs interfacial polymerization with trimesoyl chloride under the action of an organic base on the surface of an ultrafiltration membrane to obtain an alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol. The 2,2,4,4-tetramethyl-1,3-cyclobutanediol used in the present application contains a cyclobutane rigid ring structure, and has four methyl substituents on the ring, which provides steric hindrance and gives the polymer skeleton high rigidity. The polyester loose nanofiltration membrane prepared has high permeation flux and can effectively separate dyes and inorganic salts, and has strong alkali resistance, and can still exhibit excellent separation performance after being soaked in strong alkali for 48 hours. The preparation method provided by the present application is simple and easy to operate, and provides a reference direction for preparing alkali-resistant polyester nanofiltration membranes.
[0045] The present application provides a preparation method of an alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol, comprising the following steps:
[0046] 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) is dissolved in deionized water containing an organic base, stirred uniformly to obtain an aqueous solution;
[0047] Trimesoyl chloride (TMC) is dissolved in n-hexane to obtain an organic phase solution;
[0048] The aqueous solution is poured on the pretreated ultrafiltration membrane, soaked, then the remaining aqueous solution is poured out, and the residual liquid on the surface of the ultrafiltration membrane is removed to obtain an ultrafiltration membrane with uniformly distributed aqueous phase on the surface;
[0049] The organic phase solution is poured on the surface of the ultrafiltration membrane with uniformly distributed aqueous phase to perform interfacial polymerization, and after the end, the excess organic phase solution is poured out;
[0050] The ultrafiltration membrane after interfacial polymerization is subjected to heat treatment to obtain an alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol.
[0051] The application provides a method for preparing an alkali-resistant polyester loose nanofiltration membrane with high selective permeability by using 2,2,4,4-tetramethyl-1,3-cyclobutanediol as a water-phase monomer and trimesoyl chloride through an interfacial polymerization method. The water-phase monomer TMCD has a unique twisted structure and large steric hindrance. Meanwhile, the addition of an organic base to neutralize HCl generated in the reaction promotes proton transfer in the reaction, and a dense and uniform polyester separation layer is formed, so that high permeation flux and efficient separation of dyes / salts are realized, and stable separation performance can be maintained under strong alkali conditions with pH = 14.
[0052] In the preferred embodiment of the application, the mass concentration of the water-phase solution is 0.5-2%; the mass ratio of TMCD to the organic base is (1-3):(1-2), for example, the mass ratio of TMCD to the organic base is 1:1, 3:1 or 1:2.
[0053] In the preferred embodiment of the application, the organic base is selected from one of triethylamine (TEA), tripropylamine (TPA) and N,N-diisopropyl ethylamine (DIPEA).
[0054] In the preferred embodiment of the application, the mass percentage of trimesoyl chloride in the organic-phase solution is 0.1-0.3%, preferably 0.2-0.3%.
[0055] In the preferred embodiment of the application, the method for pretreating the ultrafiltration membrane is as follows: the ultrafiltration membrane is soaked in deionized water for standby, and the deionized water is replaced every 24 hours to ensure the cleanliness of the membrane surface.
[0056] In the preferred embodiment of the application, the ultrafiltration membrane is selected from one of polyether sulfone (PES) ultrafiltration membrane and polysulfone (PSF) ultrafiltration membrane, and the molecular weight cut-off of each is 100-150 KDa.
[0057] In the preferred embodiment of the application, after the water-phase solution is poured on the pretreated ultrafiltration membrane, the soaking time is 1-5 min, and preferably the soaking time is 2-5 min.
[0058] In the preferred embodiment of the application, the interfacial polymerization time is 1-10 min, and preferably the interfacial polymerization time is 5-10 min.
[0059] In the preferred embodiment of the application, the heat treatment temperature is 50-100 DEG C, and the heat treatment time is 5-15 min; preferably, the heat treatment temperature is 50-70 DEG C, and the heat treatment time is 10-15 min.
[0060] The embodiment of the application further provides an alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol, which is prepared by the preparation method.
[0061] The alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol provided by the embodiment of the application can be used for dye recovery in printing and dyeing wastewater.
[0062] The alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol provided by the embodiment of the application can be used for salt recycling.
[0063] The alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol provided by the embodiment of the application can be used for dye recovery in printing and dyeing wastewater.
[0064] Unless otherwise specified, the room temperature in the application is 25±2℃.
[0065] The raw materials used in the embodiment of the application are all commercially available.
[0066] It should be noted that the details not described in the application are all conventional operating means in the art, and are not the focus of the application.
[0067] The technical solutions of the application are further described below through examples.
[0068] Example 1
[0069] A preparation method of an alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol, the steps are as follows:
[0070] (1) The PES ultrafiltration membrane with a molecular weight cut-off of 150KDa is soaked in deionized water for standby, and the deionized water is replaced every 24 hours to ensure the cleanliness of the membrane surface;
[0071] (2) 1.0g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) and 1.0g of triethylamine are dissolved in 98.0g of deionized water to prepare a 1wt% aqueous solution (TMCD aqueous solution); 0.1g of trimesoyl chloride (TMC) is dissolved in 49.9g of n-hexane to prepare a 0.2wt% oil solution (TMC n-hexane solution);
[0072] (3) Fix the PES ultrafiltration membrane from step (1) in the frame, pour in TMCD aqueous solution, soak for 2 min, so that the membrane surface can fully absorb the aqueous solution, pour out the excess solution and blow dry the surface, pour the TMC n-hexane solution evenly on the membrane surface interface for polymerization for 5 min, place the membrane in a 60℃ oven for 10 min to promote crosslinking, and obtain an alkali-resistant polyester loose nanofiltration membrane (PE LNF) based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and store it in deionized water for later use.
[0073] The PES ultrafiltration membrane used in this embodiment and the obtained alkali-resistant polyester loose nanofiltration membrane were characterized by scanning electron microscopy.
[0074] Figure 1 This is a scanning electron microscope image of the surface of the original PES ultrafiltration membrane. Figure 2 This is a scanning electron microscope (SEM) image of the surface of an alkali-resistant polyester loose nanofiltration membrane (PE LNF). Figure 3 The images show the attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectra of the original PES ultrafiltration membrane and the alkali-resistant polyester loose nanofiltration membrane (PE LNF).
[0075] pass Figures 1-3 It can be seen that the PES ultrafiltration membrane exhibits a uniformly distributed pore structure on its surface, resulting in a relatively smooth surface. Compared to the PES ultrafiltration membrane, the polyester nanofiltration membrane obtained after interfacial polymerization of TMCD and TMC has a denser surface, indicating that TMCD and TMC have been successfully cross-linked. A 1729 cm⁻¹ diameter was observed in the infrared spectrum. -1 The new peak at this location corresponds to the tensile vibration of C=O (ester bond), indicating the successful preparation of an alkali-resistant, porous polyester nanofiltration membrane.
[0076] The performance of alkali-resistant loose polyester nanofiltration membranes was tested using the following methods:
[0077] Cross-flow filtration equipment was used to evaluate the membrane's permeation selectivity; the effective filtration area of the membrane was 15.9 cm². 2 Before filtration, the filter was pre-pressurized with pure water at 2.5 bar for 30 minutes to achieve stable flow. Subsequent tests were conducted at 2 bar.
[0078] (1) Permeability and retention properties
[0079] The pure water permeate flux (PWP) and the rejection rates (R) of inorganic salts and Congo red dye for the alkali-resistant porous polyester nanofiltration membrane were tested using pure water, Na₂SO₄ solution (2000 ppm), and Congo red solution (100 ppm) as feed solutions, respectively. The results showed that the membrane had a pure water flux as high as 221.3 L·m⁻¹. -2 ·h -1 ·bar -1The rejection rate of Na2SO4 was 6.8%, and the rejection rate of Congo red reached 99.9%.
[0080] The permeate flux and salt and Congo red rejection rates of the four salt (Na2SO4, MgSO4, MgCl2 and NaCl) and Congo red mixed solution were tested under mixed feed containing Congo red (100 ppm) and salt (2000 ppm) respectively, to further evaluate the dye / salt separation capacity of the PE LNF membrane, and the results are shown in Figure 4 The results show that the alkali-resistant polyester loose nanofiltration membrane has excellent dye / salt separation selectivity for various dye / salt mixed solutions, and the CR rejection rate of the four different mixtures reaches 99.9%, and the salt rejection rate is less than 20%. It shows that the PE LNF membrane has excellent separation selectivity.
[0081] (2) Alkali resistance
[0082] The prepared alkali-resistant polyester loose nanofiltration membrane was immersed in NaOH solution with different pH (7, 11, 12, 13, 14) for 48h, then the membrane was taken out and the membrane surface was washed with deionized water for membrane performance test. The pure water permeate flux and the rejection rate of Congo red of the polyester nanofiltration membrane of this embodiment were tested under 2bar pressure using pure water and Congo red (100 ppm) solution as feed liquid respectively. The results show that the rejection rate of PE LNF to Congo red is more than 97.6%. Figure 5 The normalized pure water flux of the alkali-resistant polyester nanofiltration membrane after soaking for 48h at different pH can be seen from Figure 5 It can be seen that the prepared alkali-resistant polyester loose nanofiltration membrane can still maintain stable permeate flux after soaking for 48h under strong alkali conditions. It shows that the prepared polyester nanofiltration membrane can still exhibit excellent permeability and Congo red solution rejection rate after strong alkali treatment.
[0083] Example 2
[0084] A preparation method of a 2,2,4,4-tetramethyl-1,3-cyclobutanediol polyester loose nanofiltration membrane, the steps are as follows:
[0085] (1) The PES ultrafiltration membrane with a molecular weight cut-off of 150KDa was soaked in deionized water for standby, and the deionized water was replaced every 24 hours to ensure the cleanliness of the membrane surface.
[0086] (2) 1.5g TMCD and 0.5g triethylamine were dissolved in 98.0g deionized water to prepare a 1.5wt% aqueous solution; 0.1g trimesoyl chloride was dissolved in 49.9g n-hexane to prepare a 0.2wt% oil solution.
[0087] (3) Fix the PES ultrafiltration membrane in the frame, pour the aqueous phase solution, soak for 5 min, make the membrane surface fully absorb the monomer solution, pour out the excess solution and blow-dry the surface; evenly pour the organic phase solution on the membrane surface, after 8 min of reaction, place the membrane in a 50°C oven for 10 min to promote crosslinking, to obtain the 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based alkaline-resistant polyester loose nanofiltration membrane, which is stored in deionized water for standby.
[0088] According to the performance test method in Example 1, pure water, Na2SO4 solution (2000 ppm) and Congo red solution (100 ppm) were respectively used as feed liquid to test the pure water permeation flux of the alkaline-resistant polyester loose nanofiltration membrane and the rejection rate of inorganic salt and Congo red dye. The results show that the pure water flux of the membrane is 210.5 L·m -2 ·h -1 ·bar -1 , the rejection rate of Na2SO4 is 5.8%, and the rejection rate of Congo red is 99.9%. It shows that the alkaline-resistant polyester loose nanofiltration membrane exhibits high water flux and excellent dye rejection rate and inorganic salt permeability.
[0089] Example 3
[0090] A preparation method of a 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane, the steps are as follows:
[0091] (1) Soak the PES ultrafiltration membrane with a molecular weight cut-off of 100 KDa in deionized water for standby, and replace the deionized water every 24 hours to ensure the cleanliness of the membrane surface.
[0092] (2) Dissolve 0.5 g of TMCD and 1.0 g of N,N-diisopropylethylamine (DIPEA) in 98.5 g of deionized water to prepare a 0.5 wt% aqueous phase solution; dissolve 0.15 g of trimesoyl chloride in 49.85 g of n-hexane to prepare a 0.3 wt% organic phase solution.
[0093] (3) Fix the PES ultrafiltration membrane in the frame, pour the aqueous phase solution, soak for 5 min, make the membrane surface fully absorb the monomer solution, pour out the excess solution and blow-dry the surface; evenly pour the organic phase solution on the membrane surface, after 8 min of reaction, place the membrane in a 50°C oven for 10 min to promote crosslinking, to obtain the 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based alkaline-resistant polyester loose nanofiltration membrane, which is stored in deionized water for standby.
[0094] The pure water permeation flux and the rejection of inorganic salt and Congo red dye of the alkali-resistant polyester loose nanofiltration membrane were tested by using pure water, Na2SO4 solution (2000 ppm) and Congo red solution (100 ppm) as feed liquid respectively according to the performance test method in Example 1. The results showed that the pure water flux of the membrane was 190.5 L·m -2 ·h -1 ·bar -1 The rejection of Na2SO4 was 6.1%, and the rejection of Congo red was 99.6%, which proved that the alkali-resistant polyester loose nanofiltration membrane exhibited high water flux and excellent dye rejection rate and inorganic salt permeation rate.
[0095] Example 4
[0096] A preparation method of a 2,2,4,4-tetramethyl-1,3-cyclobutanediol polyester loose nanofiltration membrane, the steps are as follows:
[0097] (1) The polysulfone (PSF) ultrafiltration membrane with a molecular weight cut-off of 100 KDa was immersed in deionized water for standby, and the deionized water was replaced every 24 hours to ensure the cleanliness of the membrane surface.
[0098] (2) 2 g of TMCD and 2 g of triethylamine were dissolved in 96 g of deionized water to prepare a 2 wt% aqueous phase solution; 0.15 g of trimesoyl chloride was dissolved in 49.85 g of n-hexane to prepare a 0.3 wt% organic phase solution.
[0099] (3) The PSF ultrafiltration membrane was fixed in the frame, the aqueous phase solution was poured in, and the membrane surface was soaked for 1 min to make the membrane surface fully absorb the monomer solution, the excess solution was poured out and the surface was blown dry, the organic phase solution was uniformly poured on the membrane surface, and after 1 min of reaction, the membrane was placed in a 100℃ oven for 15 min to promote crosslinking, to obtain a 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane, which was stored in deionized water for standby.
[0100] The pure water permeation flux and the rejection of inorganic salt and Congo red dye of the alkali-resistant polyester loose nanofiltration membrane were tested by using pure water, Na2SO4 solution (2000 ppm) and Congo red solution (100 ppm) as feed liquid respectively according to the performance test method in Example 1. The results showed that the pure water flux of the membrane was 193.5 L·m -2 ·h -1 ·bar -1 The rejection of Na2SO4 was 6.3%, and the rejection of Congo red was 98.2%, which proved that the alkali-resistant polyester loose nanofiltration membrane exhibited high water flux and excellent dye rejection rate and inorganic salt permeation rate.
[0101] Comparative Example 1
[0102] The method of Example 1 was followed, except that in step 2) the aqueous phase monomer was 1,4-butanediol (BDO) and the catalyst was sodium hydroxide, and a 1,4-butanediol-based polyester nanofiltration membrane (BDO-PE LNF) was prepared.
[0103] According to the alkali resistance performance test method in Example 1, the 1,4-butanediol-based polyester nanofiltration membrane was immersed in NaOH aqueous solution with different pH (7, 13, 14) for 48 h, then the membrane was taken out and the membrane surface was rinsed with deionized water for membrane performance test. Pure water and Congo red (100 ppm) solution were used as feed liquid to test the pure water permeation flux and Congo red rejection rate of the 1,4-butanediol-based polyester nanofiltration membrane. The results showed that the pure water flux of the membrane was 196.2 L·m -2 ·h -1 ·bar -1 .
[0104] Figure 6 The normalized pure water flux diagram of the 1,4-butanediol-based polyester nanofiltration membrane after immersion in different pH for 48 h, it can be seen from the diagram that the pure water permeation flux of the membrane increased significantly after strong alkali treatment. Figure 7 The feed liquid and filtrate comparison diagram of PE LNF and 1,4-butanediol-based polyester nanofiltration membrane (BDO-PE LNF) when filtering Congo solution after immersion in pH = 14 for two days, the results showed that the rejection rate of 1,4-butanediol-based polyester nanofiltration membrane to Congo red was above 59.7%. It showed that the 1,4-butanediol-based polyester nanofiltration membrane prepared was hydrolyzed in strong alkali solution, and it was difficult to achieve high-efficiency rejection of Congo red solution in strong alkali conditions. The polyester nanofiltration membrane prepared by BDO was easily hydrolyzed in strong alkali due to its straight-chain structure and exposed ester bond, causing the destruction of the membrane structure and thus losing the rejection ability to dyes.
[0105] Comparative Example 2
[0106] The method of Example 1 was followed, except that in step 2) 1.0 g TMCD and 1.0 g NaOH were dissolved in 98.0 g deionized water to prepare a 1 wt% TMCD aqueous solution, and a polyester nanofiltration membrane was obtained.
[0107] According to the performance test method in Example 1, pure water, Na2SO4 solution (2000 ppm) and Congo red solution (100 ppm) were used as feed liquid to test the pure water permeation flux and rejection rate of inorganic salt and Congo red dye of the polyester nanofiltration membrane prepared in this comparative example. The results showed that the pure water flux of the polyester nanofiltration membrane prepared in this comparative example was 331.6 L·m -2 ·h -1 ·bar -1The rejection of Na2SO4 was 5.1%, and the rejection of Congo red was 66.5%. The polyester nanofiltration membrane prepared in the present comparative example has a low rejection rate of Congo red, and it is difficult to achieve efficient separation of dyes / salts.
[0108] Table 1 shows the pure water flux and rejection rate of the polyester nanofiltration membranes prepared in Examples 1-4 and Comparative Examples 1-2.
[0109] Table 1
[0110]
[0111] As shown in Table 1, the alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol prepared in the present application has a high water flux and dye rejection rate, and a low divalent salt rejection rate. The high rejection rate of the nanofiltration membrane to dyes indicates that it can effectively prevent dye molecules from passing through, and the low rejection rate of the nanofiltration membrane to divalent salts indicates that it allows salt ions to pass through relatively easily. The difference indicates that the nanofiltration membrane has selective permeation ability to molecules or ions of different sizes, thereby proving its selectivity.
[0112] The above merely describes the preferred embodiments of the present application, but the protection scope of the present application is not limited thereto, and any person skilled in the art can easily think of changes or replacements within the technical scope disclosed in the present application, which should be covered in the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. A method for producing an alkali-resistant, 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane, characterized by, The method comprises the following steps: dissolving 2,2,4,4-tetramethyl-1,3-cyclobutanediol in deionized water containing an organic base, stirring to obtain an aqueous solution; dissolving trimesoyl chloride in n-hexane to obtain an organic phase solution; pouring the aqueous solution onto a pretreated ultrafiltration membrane, soaking, then pouring out the remaining aqueous solution, and removing the residual liquid on the surface of the ultrafiltration membrane to obtain an ultrafiltration membrane with uniformly distributed aqueous phase on the surface; pouring the organic phase solution onto the surface of the ultrafiltration membrane with uniformly distributed aqueous phase to perform interfacial polymerization, then pouring out the excess organic phase solution; subjecting the ultrafiltration membrane after interfacial polymerization to heat treatment to obtain the alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol.
2. The method for preparing an alkali-resistant 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane according to claim 1, characterized by, The mass concentration of the aqueous solution is 0.5-2%. And / or, the mass ratio of 2,2,4,4-tetramethyl-1,3-cyclobutanediol to organic base is (1-3):(1-2).
3. The method for producing an alkali-resistant 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane according to claim 2, characterized by, The organic base is selected from one of triethylamine, tripropylamine and N,N-diisopropyl ethylamine.
4. The method for preparing an alkali-resistant 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane according to claim 1, characterized by, The mass percentage of trimesoyl chloride in the organic phase solution is 0.1-0.3%.
5. The method for preparing an alkali-resistant 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane according to claim 1, characterized by, After pouring the aqueous solution onto the pretreated ultrafiltration membrane, the soaking time is 1-5 min.
6. The method for preparing an alkali-resistant 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane according to claim 1, characterized by, The interfacial polymerization time is 1-10 min.
7. The method for preparing an alkali-resistant 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based polyester loose nanofiltration membrane according to claim 1, characterized by, The heat treatment temperature is 50-100℃, and the heat treatment time is 5-15 min.
8. An alkali-resistant, 2,2,4,4-tetramethyl-1,3-cyclobutanediol-based, polyester, loose, nanofiltration membrane, characterized in that, Prepared according to the preparation method of any one of claims 1-7.
9. Use of the alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol according to claim 8 in treating printing and dyeing wastewater.
Citation Information
Patent Citations
Preparation method of polyester loose nanofiltration membrane
CN119345924A
Void-containing polyester shrink film with improved density retention
US20060121219A1
